Quantifying canine interactions with smart toys assesses suitability for service dog work - Byrne, Ceara; Starner, Thad; Jackson, Melody (Frontiers in Veterinary Science, 2022)
There are approximately a half million active service dogs in the United States, providing life-changing assistance and independence to people with a wide range of disabilities. The tremendous value of service dogs creates significant demand, which service dog providers struggle to meet. Breeding, raising, and training service dogs is an expensive, time-consuming endeavor which is exacerbated by expending resources on dogs who ultimately will prove to be unsuitable for service dog work, because of temperament reasons. Quantifying behavior and temperament through sensor-instrumented dog toys can provide a way to predict which dogs will be suitable for service dog work, allowing resources to be focused on the dogs likely to succeed. In a two-year study, we tested dogs in advanced training at Canine Companions for Independence with the toys, we discovered that a measure of average bite duration is significantly correlated with a dog’s placement success as a service dog (Adjusted OR = 0.12, Pr(>|z|) = 0.00666). Applying instrumented toy interactions to current behavioral assessments could yield more accurate meaures for predicting successful placement of service dogs while reducing the workload of the trainers.